Exploring learners’ motivation and learners’ burnout from Herzberg’s dual-factor theory - Mohd Rathi, Nor Azah; Syed Hussain, Sharifah Shahnaz; Zubir, Zurina; Ab Ghani, Haliza; Md Zamin, Ainul Azmin; Rahmat, Noor Hanim (Global Academic Excellence, 2025)
This study aims to explore learners’ motivation and burnout from Herzberg’s two-factor motivation theory. The theory explores motivation and dissatisfaction in learners. This quantitative study investigates the relationship between learners’ motivation and learners’ burnout based on Herzberg’s motivation theory. A sample of 103 respondents from Social Sciences and Science and Technology responded to the survey. Data were collected through a structured questionnaire consisting of 45 items with a five-point Likert scale survey. The findings indicate a strong positive relationship between dissatisfaction and satisfaction in all components: value, expectancy and affective. This study calls for educators to explore both motivation and burnout factors to foster intrinsic and extrinsic motivation and implement strategies to alleviate burnout